Presidential decree-law no. 44/2014 on imposing a temporary additional tax on the income = قرار رئيس جمهورية مصر العربية بالقانون رقم 44 لسنة 2014 بفرض ضريبة إضافية مؤقتة على الدخل - Egypt : Ministry of Finance. The Egyptian Customs Authority (2025)
Presidential Decree-Law No. 44 of the year 2014 on imposing a temporary additional tax on the income – قرار رئيس جمهورية مصر العربية بالقانون رقم 44 لسنة 2014 بفرض ضريبة إضافية مؤقتة على الدخل